Recognising the "Red Flags" of get-rich-quick schemes / Eley Suzana Kasim, Norlaila Md Zin and Hazlina Mohd Padil - Kasim, Eley Suzana; Md Zin, Norlaila; Mohd Padil, Hazlina (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In the late 1980s, Malaysians were shocked to find out about a get-rich-quick scheme organised by Osman Hamzah or more famously known as Pak Man Telo. He was a man from Taiping, Perak who was employed as a journalist of local newspapers in the 1960s and 1970s. His modus operandi involved setting up a company in 1972 that offered a fraudulent deposit taking activity known as Skim Pertama Berhad or Skim Pak Man Telo. In total, there were around 50,000 subscribers who contributed an estimated amount of RM90.9 million to the scheme. The scheme was very attractive at the beginning as "investors" were paid high dividend pay-out even though there was no real business model used by the perpetrator. It was not until a few months have elapsed that the depositors started to realise it was a scam and demanded they were to be refunded with their "investment" money. Since Pak Man Telo, many other get-rich-quick schemes were devised with the same aim to obtain money illegally. Unfortunately, people keep being deceived by so many versions of get-rich-quick schemes up until today. What makes it interesting is the evolution of the fraud modus operandi to keep pace with technological advancement. Nowadays, perpetrators manage to keep abreast of the latest digital technology and use it to their own advantage to cheat people such as using social media.